Formation and Surface Behavior of Pt and Pd Complexes with Ligand Systems Derived from Nitrile‐functionalized Ionic Liquids Studied by XPS. Issue 2 (20th October 2022) - Hemmeter, Daniel; Paap, Ulrike; Taccardi, Nicola; Mehler, Julian; Schulz, Peter S.; Wasserscheid, Peter; Maier, Florian; Steinrück, Hans‐Peter
Abstract: We studied the formation and surface behavior of Pt(II) and Pd(II) complexes with ligand systems derived from two nitrile‐functionalized ionic liquids (ILs) in solution using angle‐resolved X‐ray photoelectron spectroscopy (ARXPS). These ligand systems enabled a high solubility of the metal complexes in IL solution. The complexes were prepared by simple ligand substitution under vacuum conditions in defined excess of the coordinating ILs, [C3 CNC1 Im][Tf2 N] and [C1 CNC1 Pip][Tf2 N], to immediately yield solutions of the final products. The ILs differ in the cationic head group and the chain length of the functionalized substituent. Our XPS measurements on the neat ILs gave insights in the electronic properties of the coordinating substituents revealing differences in donation capability and stability of the complexes. Investigations on the composition of the outermost surface layers using ARXPS revealed no surface affinity of the nitrile‐functionalized chains in the neat ILs. Solutions of the formed complexes in the nitrile ILs showed homogeneous distribution of the solute at the surface with the heterocyclic moieties preferentially orientated towards the vacuum, while the metal centers are rather located further away from the IL/vacuum interface. Abstract : Pt and Pd complexes with ionic liquid(IL)‐derived ligands are accessible via ligand substitution from [MCl2 (CH3 CN)2 ] precursors under vacuum and are studied by XPS. Resulting complexes show a preferential orientation in IL solution with cationic moieties pointing towards the vacuum, while the metal is further away from the IL/vacuum interface.